Substance P release from rat dura mater is inversely correlated with CGRP release- experiments using glycerol trinitrate and anti-CGRP antibodies - Dux Mária (JOURNAL OF HEADACHE AND PAIN, 2025)
The neuropeptides calcitonin gene-related peptide (CGRP) and substance P are important mediators of neurogenic inflammation when they are released from activated primary nociceptive afferents. It is long evident that neuropeptides play an important role in migraine pathophysiology, but the significance of neurogenic inflammation is still debated.In an approved hemisected rodent head preparation, we measured CGRP release from the cranial dura mater in parallel with substance P release using animals pre-treated with anti-CGRP antibodies or control solutions.Apart from the known decrease in CGRP release following antibody treatment, we found a significant inverse correlation of basal and stimulated CGRP versus substance P release across all experiments. The results are discussed in connection with our previously published data.An increase in CGRP release seems to inhibit substance P release in meningeal structures possibly decreasing substance P-dependent plasma extravasation, which argues against a significant role of neurogenic inflammation in migraine.